2008
DOI: 10.1142/s021926590800214x
|View full text |Cite
|
Sign up to set email alerts
|

Divisible Load Distribution in a Network of Processors

Abstract: The paper presents a closed form solution for an optimum scheduling of a divisible job on an optimum number of processor arcanged in an optimum sequence in a multilevel tree networks. The solution has been derived for a single divisible job where there is no dependency among subtasks and the root processor can either perform communication and computation at the same time. The solution is carried out through three basic theorems. One of the theorems selects the optimum number of available processors that must p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 25 publications
(23 reference statements)
0
1
0
Order By: Relevance
“…It was shown that finding an *Corresponding author: Sameer Bataineh, Faculty of Computer and Information Technology, Jordan University of Science and Technology, Jordan, Tel: +96227201000; E-mail: samir@just.edu.jo analytical solution for general scheduling problem in a Grid is a very difficult task [24].…”
Section: Introductionmentioning
confidence: 99%
“…It was shown that finding an *Corresponding author: Sameer Bataineh, Faculty of Computer and Information Technology, Jordan University of Science and Technology, Jordan, Tel: +96227201000; E-mail: samir@just.edu.jo analytical solution for general scheduling problem in a Grid is a very difficult task [24].…”
Section: Introductionmentioning
confidence: 99%